Promotion And Distribution Strategies in Increasing Sales in The Tofu Industry Tiga “S” Prima - Donatia Trisnawati Haina; Elly Lestari; Moh. Askiyanto (International Research & Development for Human Beings (IRDH), 2026)
In the current digital age, Small and Medium Enterprises (SMEs) in Indonesia encounter major difficulties when competing against large corporations. This research seeks to examine promotional and distribution tactics for boosting sales at Tahu Tiga S Prima Industry located in Batu City. The study utilizes a qualitative methodology with a descriptive technique, gathering information through interviews, observations, and documentation. Sources consist of entrepreneurs, marketing and distribution personnel, and typical customers. The results suggest that promotional tactics include word-of-mouth advertising, radio commercials, event participation, and product sampling to capture consumer attention. Product quality is recognized as a crucial element that enhances promotional effectiveness. Simultaneously, distribution tactics are executed via direct sales, the creation of market representatives, and collaborations to enhance market penetration. The blend of successful marketing and distribution techniques has led to higher sales, market growth, and stronger customer loyalty. Nevertheless, obstacles persist, especially regarding restricted digital marketing and inadequate distribution reach. Consequently, it is advised to implement more creative and flexible marketing approaches that are in tune with technological progress and changing consumer demands